Mucositis, a side effect of a chemotherapeutical treatment: physiopathology and management - Gallego-G., Carolina (Revista Facultad de Odontología Universidad de Antioquia, 2009)
Around 40% of the patients treated with chemotherapy show oral lesions or side effects of chemotherapy agents which produce a cellular destruction of the proliferating or growing cells. These are stomatitis, xerostomy, gingivitis, trismus, dental caries, cellulitis and mainly mucositis. This last one appears between 5 or 7 days after the beginning of chemotherapy, with a maximum peak between 7 and 10 days. Oral mucositis is a biologic process divided in 4 stages that are classified according to the patient`s signs and symptoms. For its management there are several elements such as saline solution, clorhexidine, aluminium hydroxyl, sucralfate etc.; which can also be mixed with other creating the so called “magic mouthwash”, giving relief to the patient by reducing the symptoms. The present article shows a complete theme report on the subject from generalities and classifications to the different palliative treatments.